Distinction Between Dysplasia, Malformation, and Deformity—Towards the Proper Diagnosis and Treatment of Hip Development Disorders - Jacek Dygut; Monika Piwowar (Diagnostics)
(1) Background: This publication focuses on processes that disrupt the proper development of the hip. Four pathomechanisms underlying human developmental defects are described in the literature, i.e., dysplasia, malformation, disruption, and deformity. In the case of hip development, arguably the greatest challenge involves confusion between dysplasia and deformity, which often leads to misdiagnosis, incorrect nomenclature, and incorrectly chosen treatment. (2) Methods: A review of the scientific literature was performed. (3) Results: The paper presents a description of hip joint development disorders in the context of their pathomechanisms. An attempt was made to answer the question of whether these disorders are rooted in a primary disorder of tissue growth, resulting in incorrect anatomy, or are the result of anatomical deformations with secondary modifications in tissue structures—of a degenerative or adaptive nature—based on Delpech–Hueter–Volkmann growth and remodeling laws. In addition, the emphasis is placed on the presence of so-called clinically and diagnostically mute cases. We suggest augmenting diagnostic procedures with genetic tests to increase the sensitivity of screening. (4) Conclusions: Based on the arguments, a new division of developmental hip disorders is proposed.